Morphogenesis of Vomeronasal Organ of Pelophylax ridibundus (Amphibia, Anura) - Stepanyuk, Ya.V.; Kovtun, M.F. (Вестник зоологии, 2013)
The morphogenesis of the lake frog (Pelophylax ridibundus) vomeronasal organ was studied during different ontogenesis stages. The vomeronasal organ is laid after the formation of olfactory sacs, which are lined by olfactory epithelium, and after choan formation. Vomeronasal organ anlage takes place during G24 stage of larval development, which is the result of inflection and cell redistribution of olfactory epithelium rostroventral part. Formation of the vomeronasal organ finished at the beginning of metamorphosis. Apparently, vomeronasal organ appeared in aquatic Amphibia ancestors and after their transition from aquatic to terrestrial environment it developed new adaptive functions. Исследовано развитие вомероназального органа лягушки озерной (Pelophylax ridibundus) в разные периоды онтогенеза. Вомероназальный орган закладывается после образования обонятельных мешков, которые выстланы обонятельным эпителием, и хоан. Его закладка происходит на G24 стадии личиночного развития вследствие выпячивания и перераспределения клеток ростровентральной части обонятельного эпителия. Формирование вомероназального органа заканчивается в начале периода метаморфоза. Очевидно, что образование вомероназального органа состоялось в водных предков земноводных, и в результате выхода животных на сушу он приобрел новые адаптивные функции.